Method for the calculation of displacements and internal forces for a plate of arbitrary shape - A. BARYŁA (Engineering Transactions, 1980)
A method for the calculation of displacements and internal forces for a plate of arbitrary shape and under arbitrary support conditions, being under static loading, is presented. This problem has been solved on the basis of the classical linear theory of ideally elastic thin plates. A set of Fredholm's integral equations, which expressed the support conditions, was used to solve this problem.